Integrasi Teknologi Blockchain terhadap Transparansi, Akuntabilitas, dan Efisiensi dalam Sistem Pengadaan Barang dan Jasa di Sektor Maritim - Evyana Diah Kusumawati; Karjono; Karmanis (Politeknik bumi Akpelni, 2025)
The procurement system for goods and services in the maritime sector often faces serious challenges related to transparency, accountability, and efficiency, which may lead to corrupt practices and operational inefficiencies. Blockchain technology emerges as an innovative solution that offers a decentralized and immutable record-keeping system, thereby enhancing trust and integrity in procurement processes. This study aims to analyze the role of blockchain technology in improving transparency, accountability, and efficiency in the procurement system within Indonesia’s maritime sector. By using a qualitative approach, namely by collecting qualitative data through in-depth interviews with stakeholders in the maritime industry, shipping companies, port authorities, and logistics providers. The findings indicate that blockchain implementation enhances information transparency, strengthens accountability mechanisms, and accelerates processes while reducing errors in procurement. The study concludes that blockchain technology holds strategic potential to drive procurement reform in the maritime sector toward better, more efficient, and integrity-based governance.